Management of Type 2 Diabetes: Current Strategies, Unfocussed Aspects, Challenges, and Alternatives - Borse, Swapnil P.; Chhipa, Abu Sufiyan; Sharma, Vipin; Singh, Devendra Pratap; Nivsarkar, Manish (Medical principles and practice, 2021)
Type 2 diabetes mellitus (T2DM) accounts for >90% of the cases of diabetes in adults. Resistance to insulin action is the major cause that leads to chronic hyperglycemia in diabetic patients. T2DM is the consequence of activation of multiple pathways and factors involved in insulin resistance and β-cell dysfunction. Also, the etiology of T2DM involves the complex interplay between genetics and environmental factors. This interplay can be governed efficiently by lifestyle modifications to achieve better management of diabetes. The present review aims at discussing the major factors involved in the development of T2DM that remain unfocussed during the anti-diabetic therapy. The review also focuses on lifestyle modifications that are warranted for the successful management of T2DM. In addition, it attempts to explain flaws in current strategies to combat diabetes. The employability of phytoconstituents as multitargeting molecules and their potential use as effective therapeutic adjuvants to first line hypoglycemic agents to prevent side effects caused by the synthetic drugs are also discussed.